작업치료사의 근무환경이 직무만족도에 미치는 영향 : 임파워먼트의 매개효과를 중심으로 - 손보영; 방요순; 이재현 (대한작업치료학회지, 2020)
목적 : 본 연구는 병원 중심 의료기관에 종사하는 작업치료사의 근무환경과 직무만족도, 임파워먼트의 관계를 분석하고, 근무환경과 직무만족도의 관계에서 임파워먼트가 매개하는지에 대한 기초자료를 수립하고자 하였다. 연구방법 : 연구기간 및 대상은 11월 10일부터 12월 28일까지 G광역시 병원에 종사하는 작업치료사로, 총205명이었다. 근무환경, 직무만족도, 임파워먼트의 관련성은 Pearson 상관분석을 실시하였다. 근무환경, 직무만족도, 임파워먼트의 매개효과 검증은 PROCESS macro의 model 4를 적용하여 분석하였다. 간접효과의유의성 검증은 비모수 재표본(nonparametric resampling)방법으로 알려진 부트스트랩핑(bootstrapping)을 이용하였다. 결과 : 작업치료사의 근무환경, 임파워먼트, 직무만족도는 모두 유의한 양의 상관관계를 보였고, 근무환경은 직무만족도에 직접적인 영향을 주는 동시에 임파워먼트를 통해 간접적으로 영향을 미쳤다. 결론 : 작업치료사는 지시와 전달 체계에서 벗어나 직업적 특수성을 고려한 수평적이고 지지적인 탄력적 관계의 환경 조성과 자율성과 권한이 보장될 수 있는 임파워먼트의 강화가 상호작용할 때 직무만족의 향상을넘어 수준 높은 의료서비스를 기대할 수 있을 것이다. Objective: This study analyzes the relationship between an occupational therapist’s work environment, job satisfaction,and empowerment in a hospital-level medical institution. Basic data on the mediating effect of empowerment on therelationship between work environment and job satisfaction are established. Methods: The study period was from November 10 to December 28, 2018, and the subjects were 205 occupationaltherapists working in a hospital in G metropolitan city. The correlations between work environment, job satisfaction,and empowerment were analyzed using a Pearson’s correlation. The mediating effects of the work environment, jobsatisfaction, and empowerment were verified using model 4 of the PROCESS macro. The significance of the indirecteffects was verified through a non-parametric resampling method, which is also known as bootstrapping. Results: There is a statistically significant correlation between work environment, empowerment, and job satisfactionof the occupational therapists, and the work environment had both direct and indirect effects on job satisfaction withempowerment as a mediator. Conclusion: High-quality occupational therapy services can only be expected in an environment in which horizontal,supportive, and flexible relationships that are not characterized by an order and delivery system are combinedwith empowerment to guarantee both autonomy and authority. KCI Citation Count: 0